Absent Thalami Caused by a Homozygous EARS2 Mutation: Expanding Disease Spectrum of LTBL - Kevelam, Sietske H.; Klouwer, Femke C. C.; Fock, Johanna M.; Salomons, Gajja S.; Bugiani, Marianna; van der Knaap, Marjo S. (Neuropediatrics, 2016)
Leukoencephalopathy with thalamus and brainstem involvement and high lactate (LTBL) is caused by autosomal recessive EARS2 mutations. Onset is most often in infancy, but in severe cases in the neonatal period. Patients typically have magnetic resonance imaging (MRI) signal abnormalities involving the thalamus, brainstem, and deep cerebral white matter. Most signal abnormalities resolve, but in severe cases at the expense of tissue loss. Here, we report a patient with an encephalopathy of antenatal onset. His early MRI at 8 months of age showed signal abnormalities in the deep cerebral white matter that improved over time. The thalami were absent with the configuration of a developmental anomaly, without evidence of a lesion. We hypothesized that this was a case of LTBL in which the thalamic damage occurred antenatally and was incorporated in the normal brain development. The diagnosis was confirmed by a novel homozygous EARS2 mutation. Our case adds to the phenotypic and genetic spectrum of LTBL.
Keywords: EARS2; leukoencephalopathy; thalamus; mitochondrial aminoacyl-tRNA synthetase